2020
DOI: 10.38001/ijlsb.712542
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Antibiotic Resistant Bacteria from Rivers in Kelantan, Malaysia

Abstract: Antibiotic resistant bacteria have been a major concern due to the problems that they may pose in terms of public and environmental health. This present study aimed to investigate the presence of antibiotic resistance among bacterial strains isolated from rivers and to determine the impact of various human activities on the distribution of antibiotic resistant bacteria. Bacteria were isolated from river water samples of Lebir River (Point 1 and Point 2) and Kelantan River (Point 3 and Point 4). A total of 27 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…For years, a culture-dependent method would be relied upon to identify a microbial community in various settings, including the indoor air [11][12][13]. The collection of indoor air samples is a crucial step as it requires drawing a sample that represents the exposure of bacterial community which is present in the given location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For years, a culture-dependent method would be relied upon to identify a microbial community in various settings, including the indoor air [11][12][13]. The collection of indoor air samples is a crucial step as it requires drawing a sample that represents the exposure of bacterial community which is present in the given location.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on indoor air microbiomes may help to understand the potential causative agents that contribute to nosocomial infections. In the past, microbial communities in indoor air and water sources were often identi ed using a culture-dependent method [11][12][13], which involved collecting samples and culturing bacteria on agar plates using NMAM 0800 [14][15][16]. This method had limitations, including the inability to culture certain microbes and being timeconsuming.…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, the presence of Flavobacterium sp. is widely spread in freshwater habitats to the extent that some may have developed antibiotic resistance (Hassan et al, 2020). A study among the ornamental fish industry in Malaysia has also found the presence of this genus infecting fishes sold in local retail pet shops (Anjur et al, 2021).…”
Section: Importance and Application Of Bacterial Species Found In Put...mentioning
confidence: 99%
“…Because of their better biodegradability than synthetic materials, plants can also reduce treatment costs or minimize the possibility of bacteria to develop drug resistance, in addition to their alternative uses to antibiotics (Reverter et al 2014;Salikan et al 2020;Hassan et al 2020). Pitahaya is a type of climbing cactus belonging to the genus Hylocereus sp.…”
Section: Introductionmentioning
confidence: 99%